Yeast two-hybrid analysis of skeletal muscle triad junction proteins - Proenza, Catherine, author; Beam, Kurt G., advisor (Colorado State University. Libraries, 1999)
Excitation-contraction (EC) coupling in muscle is the process by which electrical stimulation releases calcium from the sarcoplasmic reticulum (SR), thereby allowing cross-bridge cycling between actin and myosin to occur. EC coupling occurs at specialized membrane regions called triad junctions. In this dissertation, the yeast two-hybrid system was used to search for interactions among known and novel proteins of triad junctions. In direct interaction tests, no strong interaction was detected between the dihydropyridine receptor (DHPR) II-III loop and the skeletal muscle ryanodine receptor (RyR); however, a possible weak interaction between physiologically important parts of the two receptors was investigated. In screens of a skeletal muscle cDNA library, no interactors were detected for the N-terminus, the I-II, II-III, or III-IV loops of the skeletal muscle DHPR. Some potential interactors of s53, of RyR1 and of junction were identified. The carboxyl terminals of both skeletal and cardiac DHPRs were extremely reactive in two-hybrid library screens. The reactive region of the skeletal DHPR was identified as residues 1621-1647. Five candidate interaction partners of the reactive region, including the glycolytic enzymes aldolase and enolase, were identified. A hypothesis for the physiological basis of the reactivity of segment E is discussed. A GFP-labeled α1s subunit truncated at residue 1620, just before the reactive region, was found to have qualitatively normal expression, current, and EC coupling when expressed in dysgenic myotubes.
Keywords: anatomy and physiology; animals; molecular biology